2021
DOI: 10.1002/cam4.4320
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of CYP2E1 is associated with poor prognosis and tumor progression of gliomas

Abstract: Objective To explore the role and possible regulatory mechanisms of CYP2E1 in gliomas. Methods RNA‑seq data and corresponding clinical information of glioma patients were collected from The Cancer Genome Atlas and Chinese Glioma Genome Atlas, and mRNA data of normal brain tissues were obtained by the Genotype‐Tissue Expression project. The Wilcoxon test was performed to analyze the correlation between CYP2E1 expression and glioma subtypes. Univariate and multivariate Cox proportional hazards regression, receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…[33][34][35][36] A previous study confirmed that CYP2E1 acts as a tumor suppressor in gliomas, consistent with our findings, suggesting that this hub gene could be a key target for follow-up studies. [37] The correlation analysis revealed that the risk score may be significantly correlated with various immunology-related parameters. Elevated expression of immune checkpoint proteins that facilitate immune escape was observed in high-risk patients with gliomas, and thus the microenvironment of high-risk patients .…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35][36] A previous study confirmed that CYP2E1 acts as a tumor suppressor in gliomas, consistent with our findings, suggesting that this hub gene could be a key target for follow-up studies. [37] The correlation analysis revealed that the risk score may be significantly correlated with various immunology-related parameters. Elevated expression of immune checkpoint proteins that facilitate immune escape was observed in high-risk patients with gliomas, and thus the microenvironment of high-risk patients .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, epigenetic modifications, which regulate the expression of several enzymes and transporters involved in drug metabolism, have been recognised as important factors that affect individual differences in clinical drug response 21 . DNA methylation affects the expression of CYP450 ( CYP1A1 , CYP1A2 , CYP1B1 , CYP2C19 , CYP2D6 , CYP2E1 and CYP2W1 ), thus leading to significant individual differences in enzyme expression 22–25 . In addition, DNA methylation regulates the expression of ABCG2 and ABCB1 , which play a crucial role in determining the success or failure of cancer chemotherapy by mediating multidrug resistance and individual differences in drug transport 26,27 .…”
Section: Discussionmentioning
confidence: 99%
“…21 DNA methylation affects the expression of CYP450 (CYP1A1, CYP1A2, CYP1B1, CYP2C19, CYP2D6, CYP2E1 and CYP2W1), thus leading to significant individual differences in enzyme expression. [22][23][24][25] In addition, DNA methylation regulates the expression of ABCG2 and ABCB1, which play a crucial role in determining the success or failure of cancer chemotherapy by mediating multidrug resistance and individual differences in drug transport. 26,27 As most studies on the methylation of genes encoding drug transporters have been carried out in the field of oncology, we investigated, for the first time, whether ABCB1 DNA methylation in donor livers affects tacrolimus blood concentrations in liver transplant recipients by regulating its expression.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, CYP2E1 activity produces acetaldehyde and ROS, increasing lipid peroxidation and promoting ferroptosis. Glioma patients with low levels of CYP2E1 have a poor prognosis since the downregulation of this gene affects lipid metabolism and prevents ferroptosis in tumor tissues, leading to glioma progression [46]. Additionally, MDM2 and MDMX promote ferroptosis in a p53-independent manner by modulating lipid activity through PPARα regulation and by inhibiting the activity of lipophilic antioxidants via FSP1 protein regulation [47].…”
Section: Lipid Metabolismmentioning
confidence: 99%